Exploring the connection between sustainable behaviors—Recycle, reuse, and reduce—and digital media framing in climate change Youtube Vodcasts - Emenyeonu C. Ogadimma; Syed Hassan Raza; Amjad Ali Shah; Shumaila Khan; Sohail Riaz; Mohammed Alkhowaiter; Sajid Ullah Khan (Sustainable Futures)
The effectiveness of digital content in promoting sustainable recycling, reusing, and reducing behaviors is largely unknown. This research used a sequential mixed-method approach to unearth the efficacy of environmental framing in digital content to foster recycling, reusing, and reducing practices that remain minimal. Study 1 analyzed YouTube content over four years, revealing that environmental issues were framed around legislation and climate change to encourage sustainable behavior. Study 2, a series of quasi-experiments with 320 African participants, tested the efficacy of these frames. The results of Study 1 revealed that climate change was the dominant frame used for digital journalistic practice, with 133 vodcasts, followed by environmental legislation with 89 vodcasts. The results of Study 2 suggested that climate change, global warming, and environmental legislation framing can result in enhancing emotional response and environmental knowledge that influence sustainable behavior. Theoretically, these results recognized that the message-consistent effects of digital content frames manifesting climate awareness and scientific evidence made viewers embrace sustainable behaviors.